Gambaran Kualitas Hidup Lansia Hipertensi di Posyandu Lansia Wonoboyo Wonogiri - Nadya Chairunisya; Eska Dwi Prajayanti (PT Pustaka Cendekia Publisher, 2026)
Hypertension among elderly individuals is a growing global concern, particularly in Indonesia where prevalence reaches 56.8% among those aged ≥60 years, often impairing quality of life across physical, psychological, social, and environmental domains. This study aimed to describe the quality of life of hypertensive elderly at Posyandu Lansia Wonoboyo, Wonogiri. A quantitative descriptive study was conducted involving a population of 387 hypertensive elderly, with a sample of 80 selected via purposive and proportional sampling using Slovin's formula. Data were collected using the WHOQOL-BREF questionnaire (26 items, Likert scale) through guided interviews, analyzed univariately with frequency and percentage via SPSS. Results showed most respondents aged 60-74 years (77.5%) and female (66.3%), with 80% reporting good quality of life. In conclusion, routine posyandu participation and family support contribute to favorable quality of life outcomes, though targeted interventions are needed for the 20% with poor ratings.